If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (3x + -2)(x + 1) = 0 Reorder the terms: (-2 + 3x)(x + 1) = 0 Reorder the terms: (-2 + 3x)(1 + x) = 0 Multiply (-2 + 3x) * (1 + x) (-2(1 + x) + 3x * (1 + x)) = 0 ((1 * -2 + x * -2) + 3x * (1 + x)) = 0 ((-2 + -2x) + 3x * (1 + x)) = 0 (-2 + -2x + (1 * 3x + x * 3x)) = 0 (-2 + -2x + (3x + 3x2)) = 0 Combine like terms: -2x + 3x = 1x (-2 + 1x + 3x2) = 0 Solving -2 + 1x + 3x2 = 0 Solving for variable 'x'. Factor a trinomial. (-1 + -1x)(2 + -3x) = 0Subproblem 1
Set the factor '(-1 + -1x)' equal to zero and attempt to solve: Simplifying -1 + -1x = 0 Solving -1 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '1' to each side of the equation. -1 + 1 + -1x = 0 + 1 Combine like terms: -1 + 1 = 0 0 + -1x = 0 + 1 -1x = 0 + 1 Combine like terms: 0 + 1 = 1 -1x = 1 Divide each side by '-1'. x = -1 Simplifying x = -1Subproblem 2
Set the factor '(2 + -3x)' equal to zero and attempt to solve: Simplifying 2 + -3x = 0 Solving 2 + -3x = 0 Move all terms containing x to the left, all other terms to the right. Add '-2' to each side of the equation. 2 + -2 + -3x = 0 + -2 Combine like terms: 2 + -2 = 0 0 + -3x = 0 + -2 -3x = 0 + -2 Combine like terms: 0 + -2 = -2 -3x = -2 Divide each side by '-3'. x = 0.6666666667 Simplifying x = 0.6666666667Solution
x = {-1, 0.6666666667}
| 3m^2+10m-13=0 | | 4x-3x-7x=x+4x-8 | | -8y-8=-7y-9 | | 8x^3-14x^2+6x=0 | | 5(3x+8)=-21+16 | | 8x^2-14x^2+6x=0 | | 4x^2-9x-5=3 | | -0.7x+0.4x+7=-8 | | -0.1=3.7 | | v+v-32.4+v+24.5=194.3 | | 2a+3b=30 | | 64t-16t^2=0 | | 0=2(x^2-3.5x-99) | | 3z-6-z+4=0 | | 24=8k+(-5k) | | (-8xy)(2xy)= | | .50x+.20y=3.15 | | 7x-x=2x+3 | | x+3x=196 | | 2=15z^2+z | | 10x^2-11x+5=0 | | 5(x-3)-(4x+3)= | | 7g=7(g-2) | | 17/3/-3/16= | | 0=2x^2-7x-198 | | 224=14(w) | | 5x-4=25 | | -x+1-2x=-4x-8 | | -11(-7)=14-9(-7) | | (5a^4+(6a+6)-a^2)-(7a-(5a^3-4a^2+5a)-6(a+6))= | | 4(x-5)=3x+5 | | 17+2y-1=10y-12-4y |